DISRUPTIVE INNOVATION: EXPLORING THE IMPACT OF SKIZA TUNES ON THE KENYAN MUSIC INDUSTRY - Kirui, Amon Kipyegon; Wanyama, Mellitus N.; Shitandi, Wilson O. (Journal of Music and Creative Arts, 2022)
This paper explores Skiza Tunes' impact on the music industry. In the process, the research sought answers on how Skiza Tunes disrupted the Kenyan music industry, the Skiza Tunes platform’s intermediary role, and its exploitative propensities. It initiates a discussion on Skiza Tunes’ disruptive innovation focusing on its business model, platform capitalism. The researcher will undertake a comprehensive literature review on platform capitalism, disruptive innovations and access-based services’ impact on the music industry. Spotify is an access-based service that thrives through platform capitalism. The researcher also conducts in-depth interviews with Kenyan artists, focussing on their opinions on the impact of Skiza Tunes on their socio-economic development. Skiza Tunes is significantly transforming the Kenyan music industry by generating new artist revenue streams. However, limited literature exists on the impact of Skiza Tunes on the music industry. Several questions still linger on the intermediary role of the Skiza Tunes, revenue splits and its exploitative propensities. There should be deliberate efforts to overhaul the education systems to reflect the current technological innovations. The skilled labour expected to drive these disruptive innovations does not get the necessary education, which slows down the adaption of these technologies in the music industry.
Keywords: Platform capitalism; disruptive innovation; ubiquitous access; royalty revenue; fourth industrial revolution